Japanese face emotions classification using lip features - Mohamad Rizon, Mohamed Juhari; Muthukaruppan, Karthigayan; Sazali, Yaacob; Nagarajan, R. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org